กระบวนการในการศึกษาข้อมูลทางประวัติศาสตร์ สังคม และวัฒนธรรม เพื่อสนับสนุนการพัฒนาชุมชนปากน้ำประแส อำเภอแกลง จังหวัดระยอง: The Process of Studying History and Socio - Culture to Support Pak Nam Prasae Community, Rayong Province Development - Laochockchaikul, Kanjana (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
This research aims to present the process of studying history and socio - culture to support Pak Nam Prasae community, Rayong Province development which focuses on 2 objectives; 1. study, collect and research to find some significant information about Pak Nam Prasae and 2. Manage data and information of Pak Nam Prasae to support community development projects. The researcher conducted filedwork with participatory action research methodology with 22 key informants and used the archaeological community cultural resource management concept. The result of this research is Pak Nam Prasae data and knowledge that the researcher and Pak Nam Prasae Community members learned, explored, and gathered stories of social capital and cultural resources in multiple aspects. In addition, activities in each process also contributed to the potential development of community members and concerned staff in every sector. The data not only inspired pride but also raised awareness of historical value and marked the start of development based on community pride and knowledge of history, social, and culture so that the community could genuinely benefit from it and put it into practice in the long-term for sustainable community development.